Amphiphilic Block Copolymer of Poly(dimethylsiloxane) and Methoxypolyethylene Glycols for High-Permeable Polysulfone Membrane Preparation - Zhang, Lei (ACS Omega, 2019)
[Image: see text] Poly(dimethylsiloxane)-block-methoxypolyethylene glycols (PDMS-b-mPEG) were synthesized by Steglich esterification. The high-permeable membrane (PSf/PDMS-b-mPEG) was prepared by using PDMS-b-mPEG as additives. The successful synthesis of PDMS-b-mPEG was confirmed by nuclear magnetic resonance. Field emission scanning electron microscopy images show that the distribution of finger-like macroporous and sponge-like macroporous can be modulated by controlling the ratio of the hydrophilic/hydrophobic components of additives. The distribution of additives and membrane wettability are validated with X-ray photoelectron spectroscopy and water contact angle test. The permeability of the blended membrane, especially for the membrane PSf/PDMS-b-mPEG1900 (M3), was remarkably improved. The water permeability of M3 (239.4 L/m(2)·h·bar) was 6.6 times that of the unblended membrane M0 (42.5 L/m(2)·h·bar). The findings of protein BSA filtration show that the flux recovery ratio of M3 is 89.2% at a BSA retention rate of about 80%, which demonstrates that the polysulfone membranes blended with PDMS-b-mPEG have excellent antifouling performance and extraordinary permeability.